Fluorescent Chromophores Containing the Nitro Group: Relatively Unexplored Emissive Properties - Chen, Meng‐Chi; Chen, Deng‐Gao; Chou, Pi‐Tai (ChemPlusChem (Weinheim, Germany), 2021)
Apart from numerous applications, for example in azo dye precursors, explosives, and industrial processes, the nitro group (−NO2) appears on countless molecules in photochemical research owing to its unique characteristics such as a strong electron‐withdrawing ability and facile conversion to the reduced substituent. Although it is well known as a fluorescence quencher, fluorescent chromophores that contain the nitro group have also emerged, with 3‐nitrophenothiazine being recently reported to have 100 % emission quantum yield in nonpolar solvents. The diverse characters of nitro‐containing chromophores motivated us to systematically review those chromophores with nitro substituents, their associated photophysical properties, and applications. In this Review, we succinctly elaborate the advance of the fluorescent nitro chromophores in fields of intramolecular charge transfer, fluorescent probes and nonlinear properties. Special attention is paid to the rationalization of the associated emission spectroscopy, so that the readers can gain insights into the structure‐photophysics relationship and hence gain insights for the strategic design of nitro chromophores. Say NO2 to quenching: The nitro group is a well‐known fluorescence quencher, however, nitro‐substituted chromophores with considerable photoluminescence quantum yields have been reported. This Review systematically organizes a number of reports concerning fluorescent nitro compounds with detailed explanations of their photophysical properties, which provides guidelines for designing emissive nitro‐containing molecules.